Selected problems of threats to the administration and the state in the context of the Russian-Ukrainian war in 2022 (Discourse of Law and Administration, 2023)
The paper focuses on the status of public administration, which is increasingly taking overthe competences of other authorities in providing basic security for citizens. The issue here are notviolations of the constitution or laws, which need to be discussed separately, but to point out that,even with formal respect for the separation of powers, we are facing profound changes that must beresilient to the state crisis. The recent accumulation of the policy of force points to a threat to theexisting paradigm of public administration, and academic reflection and analysis of legal norms donot always sufficiently capture the danger of another world war. The study draws conclusions on thegreatest dangers to firmly maintaining the systemic foundations of the separation of powers in a democraticstate of law. The main dysfunctions in the development of the Ukrainian public administration,forced to choose between freedom and sovereignty and the lives of its citizens, were also identified.In this context, the issues of information policy and the consequences of the rapid development ofinformation technology using the destruction of the population according to the so-called “Syrianmodel” are also shown. Due to the dynamics of the warfare and the impossibility to verify much ofthe information at the scene, the author relied heavily on films posted on the internet, informationpresented by the Ukrainian authorities and information from the war refugees themselves. Someof the information has been compiled from US Department of Defence (Pentagon) press releases.
Keywords: threats to the administration; threats to the state; the Russian-Ukrainian war